Hypervascularized Large Vestibular Schwannomas: Single-Center Experience in a Series of Forty Cases - Luciano Mastronardi; Alberto Campione; Fabio Boccacci; Carlo Giacobbo Scavo; Ettore Carpineta; Guglielmo Cacciotti; Raffaele Roperto; Giovanni Stati; James K. Liu (World Neurosurgery: X, 2023)
Background: Vestibular schwannomas (VS) are usually hypovascularized benign tumors. Large VS (Koos grade IV) with unusual vascular architecture are defined as hypervascular (HVVS); the excessive bleeding during microsurgery has a negative impact on results. Methods: Forty consecutive patients were operated on for HVVS (group A). A tendency to bleed and adherence of capsule to nervous structures were evaluated by reviewing intraoperative video records. The cisternal facial nerve (FN) position was reported. Microsurgical removal was classified as total, near-total, subtotal, or partial and the MIB-1 index was evaluated in all. FN results were classified according to the House-Brackmann scale. Results: Results of Group A were compared with those of 45 patients operated on for large low-bleeding VS (group B). Mean tumor diameter was 3.81 cm in group A and 3.58 cm in group B; the mean age was 42.4 and 56.3 years, respectively. The mean American Society of Anesthesiologists Physical Status Scale class of group A was 1.67 versus 2.31 of group B (P < 0.01). Total or near-total resection was accomplished in 76.5% of group A versus 73.3% of group B. Tight capsule adhesion was observed in 67.5% of group A versus 57.8% of group B. Mean MIB-1 was 1.25% and 1.08%, respectively.FN anatomic preservation was possible in 84.6% of group A versus 95.5% of group B; 67.5% of group A had HB grade I or II FN outcome versus 93.3% of group B (P < 0.001). In group A, 8 patients (20.0%) experienced transient postoperative complications versus 4.4% of group B. Recurrence/regrowth was observed in 4 patients in group A versus 1 in group B. Conclusions: Intraoperative video for classification of HVVS was used. Microsurgery of large HVVS was associated with higher (usually transient) complications and recurrence/regrowth rates and poorer FN outcome, especially in patients with tight capsule adhesion.